Influence of sugar cane bagasse ash inclusion on compacting, CBR and unconfined compressive strength of a subgrade granular material - Ojeda Farías, Omar Farid; Mendoza Rangel, José Manuel; Baltazar Zamora, Miguel Ángel (Revista ALCONPAT, 2018)
The aim of the present work was study the influence of sugar cane bagasse ash (SCBA) as a partial substitution of Compound Portland Cement (PCC) in order to enhance the properties of a granular sand soil. AASHTO standard compaction test, unconfined compressive strength test, and CBR test were made, has been compared the behavior of natural soil in study and mix with percentages of 3%, 5% and 7% of PCC as a control percentage, being carried out partial substitutions of PCC by SCBA in 0%, 25%, 50% and 100% percentages with respect to dry soil weight. The results showed enhances in the compacting, CBR and unconfined compressive strength features, reducing up to 25% the consumption of PCC.